Library 3.0 : an innovative tool in knowledge epoch - Nasirudheen, T.
Library 3.0 is the result of integration of web 3.0 technologies into the library and information services. It refers to libraries using technologies such as the semantic web, cloud computing, mobile devices and re-envisioning our use of established technologies such as federated search to facilitate user-generated content and collaboration to promote and make library collections accessible. This book comprises of 16 outstanding papers on different areas of web 3.0 and library 3.0 which have been thematically selected as - Web 3.0 & Library 3.0 Open source Library software, Knowledge Management & Data mining, Artificial Intelligence, ICT initiatives & repositories Legal, Psychological & Linguistic issues in ICT, etc. These articles have been written by prominent writers who come from different parts of India.